Geometric morphometric methods as complementary tools to investigate variability in common dolphins (Delphinus sp.) using museum specimens. (23rd October 2019) - Nicolosi, Paola; Loy, Anna
Abstract: The common dolphin ( Delphinus delphis ) has a worldwide distribution, from tropical to temperate seas and oceans. Because of the high degree of geographic variation, the taxonomy of the species is still uncertain. Skulls from 195 museum specimens from nine marine areas were examined using two‐ and three‐dimensional geometric morphometrics. Size and shape variations were analysed using univariate and multivariate statistics among and within areas. Sexual dimorphism and ontogenetic allometry were explored in the largest sample from the south‐eastern Pacific Ocean, and significant differences in size between males and females, and effects on shape from sex and marine area interactions were detected, showing that the extreme traits of larger males were a consequence of continuous growth along a common allometric trajectory. A first multivariate ordination of three‐dimensional data allowed the detection of highly derived long‐beaked morphotypes that were identified as D. delphis tropicalis . An analysis of large‐scale shape variation on two‐dimensional data in the remaining 142 short‐beaked specimens highlighted significant differences between southern and northern stocks, mainly in terms of the relative proportion of the rostrum and the braincase, suggesting an adaptive convergence irrespective of ocean of origin. The results also revealed a clear distinction in the skull shape of the north‐eastern Pacific Ocean stock and a large shape variation in the Mediterranean stock. Geometric morphometrics of the skull provided a highly accurate method to investigate the geographic variability in common dolphins, confirming previous genetic findings and highlighting new patterns of likely adaptive variations deserving further study, at both large and small geographic scales.